Prabowo Subianto's Political Branding Strategy In The Success of The Ministry of Defense's Reserve Component Program - Istiqomah, Nahdya; Angela, Deni (Dinasti Research, 2024)
Komcad is a forum and form of citizen participation as well as national facilities and infrastructure in national defense efforts. The choice of Deddy Corbuzier is closely related to Deddy Corbuzier's existence as a mentalist and YouTuber who is very close to the Zelenial Generation (Gen Z) and is a form of concern for the Ministry of Defense in facing various future challenges in the era of globalization. This research aims to provide an overview of the awarding of the title lieutenant colonel of the Indonesian Army to Deddy Corbuzier as Prabowo Subianto's Political Branding strategy in making the Ministry of Defense's Reserve Component (Komcad) program a success. This research uses a qualitative case study research method because the researcher has to answer the phenomenon of transparency and the titular rank of lieutenant colonel of the TNI AD Deddy Corbuzier as a strategy to nominate Prabowo Subianto as a presidential candidate in the 2024 elections. The results of this literature review explain that Deddy Corobuzier as Komcad ambassador is a political branding that carried out by Prabowo Subianto as Minister of Defense of the Republic of Indonesia to gain support from the younger generation to make the Komcad program a success in the context of early detection of various potential threats to Indonesia's defense system